Nitrate‐inducible NIGT1 proteins modulate phosphate uptake and starvation signalling via transcriptional regulation of SPX genes. (8th January 2020) - Ueda, Yoshiaki; Kiba, Takatoshi; Yanagisawa, Shuichi
Summary: Nitrogen and phosphorus are two major soil nutrients required for plant growth. Because requirements of both these elements are interdependent, acquisition of one must be balanced with that of the other. However, the mechanism underlying this balanced acquisition remains unclear. Here, we show by in vivo luciferase imaging that the presence of nitrogen sources is a pre‐requisite for strong activation of phosphate starvation responses. In addition, we also show that nitrate rather than ammonium is a potent modulator of phosphate starvation‐induced gene expression. Furthermore, protoplast‐based transient expression assay and chromatin immunoprecipitation assay demonstrate that NIGT1 GARP‐type transcriptional repressors, which are encoded by nitrate‐inducible genes, directly bind to and repress the promoters of genes encoding SPX proteins. Consistent with the role of SPX proteins in the suppression of the PHR1 transcriptional activator, the master regulator for phosphate starvation responses, nitrate‐dependent enhancement of phosphate starvation responses, such as accumulation of anthocyanin and promotion of root hair growth and phosphate uptake, was less evident in the nigt1.1–nigt1.4 quadruple mutant. Consistently, NIGT1 overexpression alleviated the reduction in phosphate uptake under phosphate‐replete conditions. We further reveal the intricate feedback regulations involving PHR1, NIGT1, and SPX family proteins in the phosphate starvation signalling network. Importantly, results of mutant protoplast‐based assays and in planta analysis using NIGT1 overexpression in the spx1 spx2 double mutant indicated that the NIGT1–SPX–PHR cascade mediates nitrogen status‐responsive regulation of phosphate uptake and starvation signalling. These findings uncover the mechanism underlying the balanced acquisition of nitrogen and phosphorus. Significance Statement: The nitrate‐inducible NIGT1 family proteins are responsible for coordinated uptake of nitrate and phosphate ions, two major soil nutrients for plants, but the underlying molecular pathway for the nitrogen nutrient‐induced modulation of phosphate uptake remains elusive. We found that NIGT1 family proteins suppress the expression of genes encoding SPX proteins, which negatively regulate the phosphate starvation responses and phosphate uptake, thus positively modulating phosphate starvation signalling and phosphate uptake to balance nitrate and phosphate uptake.